ETNOZOOLOGI SUKU DAYAK KANTUK UNTUK PENGOBATAN DI DESA PALAPULAU KECAMATAN PUTUSSIBAU UTARA KABUPATEN KAPUAS HULU - Dina, Kresmonika Pina; Anwari, M Sofwan; Riyono, Joko Nugroho (JURNAL HUTAN LESTARI, 2020)
The utilization of biological resour is done by humans to meet their daily needs, including as medicines, traditional ceremonies, mystical, regional arts, and hunting. Dayak Kantuk that located in Palapulau Village, Putussibau utara District, Kapuas Hulu Regency is a Dayak tribe that still runs the cultural values inherited from their ancestors by generation. One of the cultures that still run until now is the use of animals as medicine. The purpose of this research is to get data of animals species that used as medicine, body parts used, how to process and how to use them. The method used the survey method. The selection of respondents conducted by snowball sampling techniques and data collection used the questionnaire. This research was obtained by 13 respondents and acquired 20 animals species from 18 families used as a medicine by Dayak Kantuk community. The body parts used for medecine are the whole body, flesh, bile, fats, blood, scales, and Geliga. The Processed there animal varies, which are dried, boiled, burned, and fried. Used the animal’s body parts which are drinkable, applied, eaten, and used as a dish.Keywords: Dayak Kantuk, Ethnozoology, Medicine, Local Wisdom